The role of a small posterior malleolar fragment in trimalleolar fractures: a biomechanical study. (January 2018) - Evers, J.; Fischer, M.; Zderic, I.; Wähnert, D.; Richards, R. G.; Gueorguiev, B.; Raschke, M. J.; Ochman, S.
Abstract : Aims: The aim of this study was to investigate the effect of a posterior malleolar fragment (PMF), with < 25% ankle joint surface, on pressure distribution and joint-stability. There is still little scientific evidence available to advise on the size of PMF, which is essential to provide treatment. To date, studies show inconsistent results and recommendations for surgical treatment date from 1940. Materials and Methods: A total of 12 cadaveric ankles were assigned to two study groups. A trimalleolar fracture was created, followed by open reduction and internal fixation. PMF was fixed in Group I, but not in Group II. Intra-articular pressure was measured and cyclic loading was performed. Results: Contact area decreased following each fracture, while anatomical fixation restored it nearly to its intact level. Contact pressure decreased significantly with fixation of the PMF. In plantarflexion, the centre of force shifted significantly posteriorly in Group II and anteriorly in Group I. Load to failure testing showed no difference between the groups. Conclusion: Surgical reduction of a small PMF with less than 25% ankle joint surface improves pressure distribution but does not affect ankle joint stability. Cite this article: Bone Joint J 2018;100-B:95–100.